International Law and Pollution - Magraw, Daniel Barstow (University of Pennsylvania Press, 2016)
The topic of the essays in this book, the threat posed to our environment by various sources and types of pollution, is a matter of serious and growing concern. The contributors are leading international experts from a variety of legal systems and backgrounds and include Andronico Adede, Ian Brownlie, Pierre-Marie Dupuy, Johan Lammers, and Paul Szasz. International Law and Pollution provides an overview of international legal principles and institutional efforts relevant to pollution and then focuses on two particularly acute problems: nuclear pollution and acid rain. A variety of substantive issues must be confronted in order to deal with the full range of international pollution, and various institutional approaches must be utilized in the prevention, cleanup, and compensation efforts. For example, pollution from nuclear accidents results from a single event, whereas acid rain is a product of chronic emissions; the legal and policy concerns differ accordingly. In the overview, Daniel Barstow Magraw discusses fundamental concepts of international pollution, analytic distinctions among types of pollution, paradigmatic responses to pollution, and the relationship among environmental protection, economic development, and human rights. Other authors examine the existing and evolving principles of customary international law relevant to pollution, the U.N. International Law Commission's work on international liability and international watercourses, and a practitioner's perspective. The chapters on nuclear pollution analyze the conventional regimes and customary principles applicable to this field (including the Chernobyl disaster) and the determination and measurement of damages. Finally, the chapters on acid precipitation summarize the scientific background of the problem and present the multilayered European efforts to control acid rain as well as the Canada-United States acid rain controversy. International Law and Pollution will be of interest to scholars and students of environmental law and international law.